Masjid Al Ilham Pati: Membumikan Ecotheology Ramah Lingkungan dan Pemberdayaan Masyarakat Pesisir: Al Ilham Mosque, Pati: Grounding Environmentally Friendly Ecotheology and Empowering Coastal Communities - Maria Ulfah Anshor; Kustini Kosasih; Siti Atieqoh; Ida Rosyidah; Iklilah Muzayyanah DF (Jurnal Bimas Islam, 2026)
Coastal abrasion and environmental degradation pose serious challenges to sustainable development in Indonesia. Mosques, as centers of worship and social life, hold strategic potential in fostering ecological awareness among communities. This study explores the implementation of ecotheology at Jami’ Al-Ilham Mosque, Bakalan Village, Pati, which integrates Islamic values with environmentally friendly practices and coastal community empowerment. Using a qualitative case study approach, data were collected through observation, interviews, and documentation, and analyzed thematically. Findings reveal that ecotheology at Al-Ilham Mosque is grounded in scriptural texts (Qur’an, Hadith, and scholarly views) as well as ethical principles of Islam emphasizing compassion and sustainability. Implementation is realized through the Sedekah Rongsokan (scrap donation) program, employing spiritual, cultural, and structural approaches that transform waste into both religious charity and economic empowerment. Plastic and shell waste are recycled into useful products, reinforcing synergy between ecology, economy, and spirituality. Al-Ilham Mosque has become a national model, receiving the AMPeRa Green Mosque Award from the Indonesian Ministry of Religious Affairs in 2024. The study highlights the mosque’s role as a socio-ecological agent, linking Islamic spirituality with concrete environmental preservation efforts, while supporting the achievement of the Sustainable Development Goals (SDGs). Academically, this research strengthens Islamic ecotheology literacy and provides a reference for policy development on environmentally sustainable mosques in coastal regions.